Ecological restoration success: a policy analysis understanding. Issue 3 (9th February 2016) - Baker, Susan; Eckerberg, Katarina
Abstract : This article discusses how ecological restoration success can be understood and evaluated using a policy analysis lens. First, this article details a conceptual tool that helps to develop a more encompassing set of criteria to assess restoration activities that provide socioeconomic benefits. Second, by broadening the understanding of restoration success and how it can be evaluated, it allows a more critical view of evaluation itself and its uses as a policy tool. A table is presented that can help practitioners reveal preferences and clarify the aims and objectives of particular initiatives. The table also sensitizes practitioners to the complexity of the links between restoration rationales and evaluation criteria, which in turn may open up much needed discussion and dialogue between restoration participants about the underlying values an actor may wish to promote. It heightens awareness of the fact that evaluation methods need to recognize that restoration is driven by multiple rationales often in the same project, both process driven and output oriented, which in turn can change over time. Adding process and output criteria together may also raise issues of priority. Evaluation criteria thus need to be assigned in ways that reflect these multiplicities, while at the same time recognizing that some restoration values might be conflictual and that there may be winners and losers. Furthermore, judgement about "failure" of a project can change as new goals emerge in delivery and implementation. Ecological restoration evaluation should therefore be ongoing, contextual, and not a one‐off event.